IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT GOALS INTO TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING CURRICULA: REGIONAL DIFFERENCES IN SOUTHEAST ASIA AND SOUTH ASIA - Wickramasinghe, G.L.D.; Wickramasinghe, Vathsala (UI Scholars Hub, 2026)
The implementation of Sustainable Development Goals (SDGs) into curricula is within the current discourse of education for sustainable development to maintain a curriculum relevant to SDGs. We present findings of a research study that investigated the implementation of SDGs into Technical and Vocational Education and Training (TVET) curricula in the Global South - Southeast Asia and South Asia. The objectives of the paper are to present findings on 1) the implementation of nine (9) SDGs into TVET curricula, namely, 1 – ‘No Poverty’, 2 – ‘Zero Hunger’, 3 – ‘Good Health and Well-being’, 10 – ‘Reduced Inequalities’, 11 – ‘Sustainable Cities and Communities’, 12 – ‘Responsible Consumption and Production’, 14 – ‘Life below Water’, 15 – ‘Life on Land’, and 16 – ‘Peace, Justice, and Strong Institutions’, b) the use of vertical and horizontal approaches for the implementation of SDGs into curricula, and c) the existence of significant differences in the implementations in terms of the geographic location of the countries in the Global South - Southeast Asia and South Asia. This explanatory research study was conducted in 11 countries in Southeast Asia (6) and South Asia (5), building on the positivist research paradigm. Data were collected by surveying TVET teachers engaged in tertiary-level science, technology, engineering, and mathematics (STEM) programmes. Total of 761 responses collected. The findings showed that by using both vertical and horizontal approaches, institutions were committed to implementing the nine SDGs. Still, the hypothesis testing showed that significant differences prevail in the implementation between Southeast Asia and South Asia. The differences by the geographic region of a country imply that regional context, even within the Global South, is a vital consideration when assessing a country’s skill development systems. The findings have ample implications for research, practice, and policymaking not only in the Global South but also in the Global North.